Zinc finger protein 637 protects cells against oxidative stress-induced premature senescence by mTERT-mediated telomerase activity and telomere maintenance - Gao, B (Nature Publishing Group, 2014)
Oxidative stress is believed to be an important inducer of cellular senescence and aging. Zinc finger protein 637 (Zfp637), which belongs to the Krüppel-like protein family, has been hypothesized to play a role in oxidative stress. Nevertheless, the precise function of Zfp637 has seldom been reported, and it remains unclear whether Zfp637 is involved in oxidative stress-induced premature senescence. In this study, we show that the endogenous expression levels of Zfp637 and mouse telomerase reverse transcriptase (mTERT) are downregulated during oxidative stress-induced premature senescence and in senescent tissues from naturally aged mice. The overexpression of Zfp637 markedly increases mTERT expression and telomerase activity, maintains telomere length, and inhibits both H(2)O(2) and D-galactose-induced senescence accompanied by a reduction in the production of reactive oxygen species (ROS). In contrast, the knockdown of Zfp637 significantly aggravates cellular senescence by downregulating mTERT and telomerase activity, accelerating telomere shortening, and increasing ROS accumulation. In addition, the protective effect of Zfp637 against premature senescence is abrogated in the absence of mTERT. We further confirm that Zfp637 binds to and transactivates the mTERT promoter (−535/−502) specifically. As a result, the mTERT-mediated telomerase activity and telomere maintenance are responsible for the protective effect of Zfp637 against oxidative stress-induced senescence. We therefore propose that Zfp637 prevents oxidative stress-induced premature senescence in an mTERT-dependent manner, and these results provide a new foundation for the investigation of cellular senescence and aging.